The Anesthetic Technique for Clavicle Surgery in Remote Areas: Clavicopectoral Plane Block With Landmark Technique - Zammara, Abdurrahman (Direktorat Riset dan Pengabdian Kepada Masyarakat, Institut Teknologi Sepuluh Nopember, 2024)
Clavicopectoral plane block (CPB) is a relatively new regional anesthesia technique for clavicle fracture surgery. Methods: The study includes three cases of patients undergoing clavicle fracture surgery who received CPB in remote area. Results: The results show that CPB effectively prevents pain and provides high patient satisfaction. There were no complications during surgery, and pain scores remained low in the post-anesthesia care unit. Conclusions: This serial case reports suggest that CPB can be a safe and effective alternative to regional anesthesia for clavicle surgery, particularly in patients with midshaft clavicle fractures. However, further research with larger sample sizes is needed to confirm the effectiveness of CPB in clavicle surgery. Overall, CPB shows potential as a valuable technique in clavicle fracture surgery.